Seismic Response Time-Frequency Analysis of Bedding Rock Slope - Zhang, Liang; Yang, Changwei; Ma, SuJian; Guo, Xueyan; Yue, Mao; Liu, Yang (Frontiers in Physics, 2020)
According to the potential disaster points of rock bedding slope with weak structural plane along the Sichuan Tibet railway, the shaking table test of earthquake simulation is designed and carried out. The acceleration response and displacement response of slope under different input earthquake conditions are monitored, and the HHT method is mainly used to analyze the seismic response of slope. The results show that the rock bedding slope shows obvious "elevation effect" and "surface effect" under the action of seismic waves of different intensities. With the increase of the amplitude value of the input earthquake, the elevation effect and the surface effect gradually weaken. When the amplitude of seismic wave reaches 0.9g, the movement inconsistency of slope on both sides increases, and the slope is gradually separated from the main body of the slope, resulting in slope instability. The characteristics of the seismic signal in time - frequency domain can be better described by the Hilbert-Huang transform. In the time domain, the energy is mainly concentrated in 2-6s and 12-15s, and excellent frequency band is concentrated between 5hz-20hz and 30-80hz. With the increase of elevation, the former increases and the latter decreases. In addition, the change of the peak value of the marginal spectrum can clearly show the development process of the earthquake damage inside the slope. At the height of 100cm, the inflection point can be seen obviously in the slope. It shows that the damage occurs at the height of 100cm, and the degree of earthquake damage near the slope is stronger than that inside the slope. The recognition results of marginal spectrum are in good agreement with the experimental results.